Determination of Total Flavonoid Content and antibacterial activity of Nanogel combination of Red Betel Leaf and Tapak Liman - Hanun Aishy Marwa; Nadine Ayu Syaima Gustaf Prins; Alliva Ro'ain Abbiyu Imanita; Fania Putri Wiba Maharani; Rahmawati Salsa Dinurrosifa (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2026)
Flavonoids are secondary metabolites with antioxidant, antibacterial, and anti-inflammatory properties. This study aimed to determine the total flavonoid content of red betel (Piper crocatum) and tapak liman (Elephantopus scaber L.) extracts and to formulate them into nanogel preparations. Extraction was carried out by maceration using 70% ethanol, and total flavonoid content was measured by UV-Vis spectrophotometry with quercetin as the standard. The results showed that red betel extract contained the highest flavonoid level (75.15 ± 0.55 mg QE/g), while tapak liman extract had 22.10 ± 0.25 mg QE/g. The combined nanogel formulations contained 39.66–40.30 mg QE/g of flavonoids and met topical preparation standards, with Formula 2 showing the most optimal characteristics (particle size ±255 nm, physiological pH, good homogeneity). Antibacterial testing confirmed that all formulas inhibited Staphylococcus aureus, with Formula 3 exhibiting the strongest activity. These findings indicate that red betel and tapak liman extracts can be successfully developed into nanogel formulations as promising modern herbal preparations.